2021
DOI: 10.3390/rel12090678
|View full text |Cite
|
Sign up to set email alerts
|

‘When the Waves Roll High’: Religious Coping among the Amish and Mennonites during the COVID-19 Pandemic

Abstract: Religious beliefs, practices, and social support facilitate coping with psychologically distressful events and circumstances. However, COVID-19 and governmental mandates for social distancing and isolation make in-person communal forms of religious coping difficult. While some congregations began holding virtual rituals, this was not an option for Amish and conservative Mennonite groups that restrict communication and media technologies as a religious sacrament. Governmental mandates placed a disproportionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…The data used in this study provide an unparalleled lens into the lives of the Amish and Mennonites during the COVID-19 pandemic. More research is needed on how members of these communities cope with the pandemic, given limited opportunities for interaction (DiGregorio et al, 2021 ) and how they adapt to the availability of a COVID-19 vaccine (Scott et al, 2021 ; Stein et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data used in this study provide an unparalleled lens into the lives of the Amish and Mennonites during the COVID-19 pandemic. More research is needed on how members of these communities cope with the pandemic, given limited opportunities for interaction (DiGregorio et al, 2021 ) and how they adapt to the availability of a COVID-19 vaccine (Scott et al, 2021 ; Stein et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the onset of the COVID-19 pandemic, Amish and Mennonite scribes described putting their faith and trust in God in their written submissions to The Budget , an Amish and Mennonite correspondence newspaper (DiGregorio et al, 2021 ). The scribes emphasized how the pandemic created an opportunity to recenter values, slow down, and focus on relationships in the family and community.…”
Section: Covid-19 In Amish and Mennonite Groupsmentioning
confidence: 99%
“…In a study of how Amish and Mennonites coped with COVID‐19, DiGregorio et al. ( 2021 ) found that the most common religious problem‐solving approach was collaborative—indicating that people should trust and pray to God but also do their part to stop the spread of COVID‐19. In this sense, religious and medically recommended responses to COVID‐19 are not necessarily mutually exclusive or zero‐sum.…”
Section: Connections Between Medically Recommended and Religious Resp...mentioning
confidence: 99%